Nghiên cứu một số hợp chất thứ cấp từ chủng xạ khuẩn Streptomyces sp. (G065) - Danh, Cao Đức; Nam, Vũ Văn; Mai Hương, Đoàn Thị; Quyên, Vũ Thị; Hồng Minh, Lê Thị; Murphy, Brian T.; Thạch, Trần Đăng; Minh, Châu Văn; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2017)
Eight secondary metabolites, Cyclo-(Pro-Ala) (1), Cyclo-(Pro-Val) (2), Cyclo-(Pro-Leu) (3), Cyclo-(Pro-Tyr) (4), Cyclo-(Pro-Trp) (5), n-butyl-isobutyl phthalate (6), phenylacetic acid (7) and uracil (8) were isolated and identified from Streptomyces sp. (G065). Their structures were determined by spectroscopic analysis including MS and 2D NMR, as well as by comparison with reported data in literature. Keywords. Streptomyces sp., marine microorganism, Cyclo-(Pro-Ala), Cyclo-(Pro-Val), Cyclo-(Pro-Leu), Cyclo- (Pro-Tyr), Cyclo-(Pro-Trp).